Educational Marketing Innovation in Overcoming Competition Challenges and Increasing PPDB at SD Muhammadiyah 3 Pandaan: Inovasi Pemasaran Pendidikan Dalam Mengatasi Tantangan Persaingan dan Meningkatkan PPDB di SD Muhammadiyah 3 Pandaan - Rakhma, Rakhmatusakdiyah; Hidayatulloh (Indonesian Journal of Innovation Studies, 2026)
In the digital era, educational institutions face severe market competition and structural policy changes, requiring strategic adaptation to maintain institutional sustainability. However, private Islamic elementary schools often struggle with limited visibility, intense local competition, and ineffective student enrollment strategies. This study aims to analyze educational marketing innovations, competitive challenge strategies, and marketing effectiveness in boosting student enrollment at SD Muhammadiyah 3 Pandaan. Applying a descriptive qualitative approach with data collected via interviews, observations, and documentation, the study highlights marketing innovations including social media utilization, unique program offerings such as the Class International Program and Quranic boarding systems, alongside a streamlined single-day enrollment system. The findings demonstrate a significant increase in competitive standing and a substantial growth in student admissions over four consecutive academic years. Consequently, integrating multi-channel digital marketing with specialized academic-spiritual product differentiation presents a highly effective paradigm for educational institution sustainability. These findings offer practical frameworks for private primary schools to enhance market position and enrollment efficiency in competitive educational sectors. Key Findings Highlights Social media integration and specialized academic-spiritual programs drive effective institutional marketing innovation. Structured internal human resource development combined with community-based branding effectively mitigates local competitive pressures. Streamlined admission systems and flexible pricing models directly correlate with sustained multi-year enrollment growth. Keywords: Educational Marketing Innovation, Institutional Competitiveness, Student Enrollment Strategies, Islamic Elementary Education, Market Differentiation